Predicting Water Resource Impacts of Unconventional Gas Using Simple Analytical Equations. Issue 3 (12th December 2016) - Cook, P.G.; Miller, A.; Shanafield, M.; Simmons, C.T.
Abstract: The rapid expansion in unconventional gas development over the past two decades has led to concerns over the potential impacts on groundwater resources. Although numerical models are invaluable for assessing likelihood of impacts at particular sites, simpler analytical models are also useful because they help develop hydrological understanding. Analytical approaches are also valuable for preliminary assessments and to determine where more complex models are warranted. In this article, we present simple analytical solutions that can be used to predict: (1) the spatial extent of drawdown from horizontal wells drilled into the gas‐bearing formation, and rate of recovery after gas production ceases; (2) the potential for upward transport of contaminants from the gas‐bearing formation to shallow aquifers during hydraulic fracturing operations when pressures in the gas‐bearing formation are greatly increased; and (3) the potential downward leakage of water from shallow aquifers during depressurization of gas‐bearing formations. In particular, we show that the recovery of pressure after production ceases from gas‐bearing shale formations may take several hundred years, and we present critical hydraulic conductivity values for intervening aquitards, below which the impact on shallow aquifers will be negligible. The simplifying assumptions inherent in these solutions will limit their predictive accuracy for site‐specific assessments, compared to numerical models that incorporate knowledge of spatial variations in formation properties and which may include processes not considered in the simpler solutions. Abstract : Article impact statement : Simple analytical solutions are presented to provide preliminary estimates of water resource impacts of unconventional gas development.